Altered top-down and bottom-up processing of fear conditioning in panic disorder with agoraphobia. Issue 2 (23rd April 2013) - Lueken, U.; Straube, B.; Reinhardt, I.; Maslowski, N. I.; Wittchen, H.-U.; Ströhle, A.; Wittmann, A.; Pfleiderer, B.; Konrad, C.; Ewert, A.; Uhlmann, C.; Arolt, V.; et al.
Abstract : Background: Although several neurophysiological models have been proposed for panic disorder with agoraphobia (PD/AG), there is limited evidence from functional magnetic resonance imaging (fMRI) studies on key neural networks in PD/AG. Fear conditioning has been proposed to represent a central pathway for the development and maintenance of this disorder; however, its neural substrates remain elusive. The present study aimed to investigate the neural correlates of fear conditioning in PD/AG patients. Method: The blood oxygen level-dependent (BOLD) response was measured using fMRI during a fear conditioning task. Indicators of differential conditioning, simple conditioning and safety signal processing were investigated in 60 PD/AG patients and 60 matched healthy controls. Results: Differential conditioning was associated with enhanced activation of the bilateral dorsal inferior frontal gyrus (IFG) whereas simple conditioning and safety signal processing were related to increased midbrain activation in PD/AG patients versus controls. Anxiety sensitivity was associated positively with the magnitude of midbrain activation. Conclusions: The results suggest changes in top-down and bottom-up processes during fear conditioning in PD/AG that can be interpreted within a neural framework of defensive reactions mediating threat through distal (forebrain) versus proximal (midbrain) brain structures. Evidence is accumulating that this network plays a key role in the aetiopathogenesis of panic disorder.